Desenvolvimento de um sistema de documentação para o projeto de máquinas agrícolas: modelo de referência - Gassen, José Renê Freitas (2008)
The agricultural machinery design process is characterized by the transformation of elevated number abstract information in a physical model. This work presents the development of a Documentation System for the Design of Agricultural Machinery along the stages of planning and design of the Model of Reference for the Agricultural Machinery Development Process, which will be used like standard model in the execution of these projects. The methodology adopted was the employment of researches of the descriptive and exploratory kind about matters concerning the subject of the work, among them: model of reference for the agricultural machines development process; modeling of information; management of the knowledge; projects documentation systems; and, management of the communications. The specific objectives reached was definition and classification of the kinds documents, establishment of the form of presentation and of the content of each document, definition of technical way for presentation of the documents, definition of the architecture of the Design Documentation System, modeling of the documents of project and integration of the Design Documentation System to the Model of Reference for the Agricultural Machinery Development Process. The result obtained permitted the definition of three base models kinds: (i) Models of documents for alfa-numerical elements, forms and graphics; (ii) Models of documents for representative plans; and, (iii) Models of documents for illustration of technical drawings. The structure of the system of documentation developed in this work can be deployment in two parts, one with the management documents and another with the technical documents, jointly with term of opening and tutorial. It was obtained the definition, classification, relation with the domains of the knowledge and establishment of specific content for one hundred and thirty-six documents, of the which, fifty-four are of management nature and eighty-two of technical nature.